HUBUNGAN ANTARA MOTIVASI BERPRESTASI DAN PENILAIAN TERHADAP PEMBINAAN PROFESIONAL DENGAN KEMAMPUAN MENGAJAR GURU: Suatu Studi Pada Guru-guru Sekolah Dasar Di Kecamatan Ngemplak, Kabupaten Sleman, Daerah Istimewa Yogyakarta (2011) - Wartomo Wartomo (Universitas Ahmad Dahlan, 2013)
The research is aimed at determine the relationship of achievement motivation and assesment towards the guidance for teacher’s professionalism on the teacher’s teaching ability. The research was done in Ngemplak, Sleman, Yogyakarta. The number of population is all elementary school teachers, while the number of the samples is 50 teachers taken using simple random sampling. The instruments used were: (1) observation checklist for getting the data of teacher’s teaching ability, and (2) questionnaires for achievement motivation and assesment towards the guidance for teacher’s professionalism. The data were analyzed quantitatively by using simple and multiple correlation and regression. The result showed that: there is a positive correlation between achievement motivation (X1) and assessment towards the guidance for teacher’s professionalism (X2) simultaneously and teacher’s teaching ability (Y), (ry12 =0.62 and r2 =0,38 ). Based on the results, it can be stated that the ability of teachers can be improved by improving achievement motivation and developing the assessment of the professional teachers.